Plant-Derived Exosomes as a Drug-Delivery Approach for the Treatment of Inflammatory Bowel Disease and Colitis-Associated Cancer - Ying Cai; Luoxin Zhang; Youjian Zhang; Rong Lu (MDPI AG, 2022)
Inflammatory bowel disease (IBD) is a chronic recurrent intestinal disease and includes Crohn's disease (CD) and ulcerative colitis (UC). Due to the complex etiology of colitis, the current treatments of IBD are quite limited and are mainly concentrated on the remission of the disease. In addition, the side effects of conventional drugs on the body cannot be ignored. IBD also has a certain relationship with colitis-associated cancer (CAC), and inflammatory cells can produce a large number of tumor-promoting cytokines to promote tumor progression. In recent years, exosomes from plants have been found to have the ability to load drugs to target the intestine and have great potential for the treatment of intestinal diseases. This plant-derived exosome-targeting delivery system can load chemical or nucleic acid drugs and deliver them to intestinal inflammatory sites stably and efficiently. This review summarizes the pathophysiological characteristics of IBD and CAC as well as the application and prospect of plant exosomes in the treatment of IBD and CAC.